2020
DOI: 10.30587/postulat.v1i2.2094
|View full text |Cite
|
Sign up to set email alerts
|

Pengembangan Alat Evaluasi Pembelajaran Matematika Berbasis Two Tier Multiple Choice Menggunakan Ispring Suite 9

Abstract: In the era of the industrial revolution 4.0 and the pandemic era, innovation is needed in thedevelopment of technology-based evaluation tools. One of them is the ispring suite 9. Evaluation tool isimportant because it can help the process of evaluating educators to find out information on theachievement of results during the learning process. In addition to learning outcomes, evaluation can alsodetermine the ability of students to understand concepts. One of them is a two tier multiple choiceevaluation test. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
4

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
3
0
4
Order By: Relevance
“…Setelah mendapatkan penilaian dari validator ahli. Adapun range persetase validitas oleh Rovita (2020).…”
Section: Metodeunclassified
See 2 more Smart Citations
“…Setelah mendapatkan penilaian dari validator ahli. Adapun range persetase validitas oleh Rovita (2020).…”
Section: Metodeunclassified
“…Pemberian tes menggunakan bentuk multiple choice sudah menjadi pilihan yang tepat. Namun, penggunaan pilihan ganda seringkali membuat peserta didik terkadang asal memilih jawaban tanpa mengetahui alasannya (Rovita, 2020). Mata pelajaran matematika dalam proses pengerjaan memilih jawaban membutuhkan alasan tertentu.…”
unclassified
See 1 more Smart Citation
“…From several studies, it was found that assessment instruments using online and offline applications such as Socrative, Wordwall, Blocet.com, Quiz star, Google forms, Kahoot, Edmodo, Dokeos, Schoology, and Adobe Flash CS6 are feasible to be applied to measure students' cognitive abilities and used as a component that is inseparable from the learning process so that the results are more effective and efficient (Awiria et al, 2022). Various types of evaluation tools available on roaming machines can be used to make assessments successful in online learning (Rovita et al, 2020). Mondry (2008) states that an evaluation tool that is carried out online aims to be able to measure students' abilities through media that can be accessed anywhere without considering the time and place constraints.…”
Section: Introductionmentioning
confidence: 99%
“…This application can not only be used to make evaluation tools but also can be used to create learning media. Several previous researchers used the Ispring Suite in the implementation of the online evaluation process such as (Cahyanti et al, 2019), dan (Rovita et al, 2020). Some of the advantages of computer-based evaluation are that it allows giving questions to each student differently because it has the facility to randomize questions.…”
mentioning
confidence: 99%